Effect of supply chain integration on the business performance and competitiveness of the Philippine small and medium enterprises - Elaine Q. Borazon; Vivien T. Supangco (Philippine Institute for Development Studies (PIDS), 2018)
This study aims to determine the effect of supply chain integration on the business performance and competitiveness of Philippine small and medium enterprises. A survey of 384 small and medium enterprises was done and structural equation modeling was used to test the hypothesis. Results show that internal integration strongly influences (p<0.001) both business performance (growth) and competitiveness of small and medium enterprises. Moreover, customer integration influences business performance (growth). It also mediates the effect of supplier and customer integration in business performance (growth) and competitiveness of small and medium enterprises.
Keywords: 330; Supply chain integration; SMEs; competitiveness; business performance